The influence of Dexmedetomidine as an additive to local anesthetics in dental procedures: A systematic review - Diniz, Demóstenes Alves; de França, Arthur José Barbosa; Laureano-Filho, José Rodrigues; Pellizzer, Eduardo Piza [UNESP]; de Moraes, Sandra Lúcia Dantas; Vasconcelos, Belmiro Cavalcanti Do Egito (Medicina Oral, S.L., 2025)
Background: This review aimed to assess if the use of dexmedetomidine as an additive to local anesthetics pro-motes greater safety and efficacy than local anesthetics alone in dental procedures. Material and Methods: the systematic review was structured according to the PICO strategy and adhered to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) checklist. Studies were included based on the eligibility criteria, and data from the included studies were collected by one author. An additional author reviewed the compilation. Altogether, nine studies were included: eight randomized clinical trials and one controlled clinical trial. Of these, six were related to tooth extraction. Most studies reported the use of lidocaine as the local anesthetic. Levobupivacaine was used in one study. Results: In total, 352 patients were evaluated. Despite the heterogeneity between studies, it can be suggested that when used as an additive to local anesthetics, dexmedetomidine has the potential to decrease postoperative pain and latency period and prolong anesthetic duration. Conclusion: There are scant reviews that summarizes the effectiveness of dexmedetomidine as an adjuvant to local anesthetics. These studies can positively impact the lives of the concerned population.
Keywords: adjuvants anesthesics; Anesthetics; dexmedetomidine; oral surgery; systematic review